Entre prosopographie et micro-histoire : l’apport de l’approche biographique à l’histoire des ingénieurs des États de Languedoc au xviiie siècle - Catherine Isaac (Les Cahiers de Framespa)
This paper presents the methodology implemented to investigate on the engineers hired by the États (local assembly) of the province of Languedoc (South-West of France) during the 18th century to build numerous bridges and perform roadworks, between prosopography and micro-history. The first phase consisted in drawing up a list of all the involved individuals. No source enabling a global view was available. Subsequently an inductive approach based on the collection of biographical data was adopted. This research focused on their scientific and technical skills aimed at making out engineers’ education, their expertise, their tasks and achievements.